PEMANFAATAN KOTORAN BABI MELALUI KOMPOSTING DAN PENGARUHNYA TERHADAP PERTUMBUHAN LOMBOK RAWIT (CAPSICUM FRUTESCENS) - I W. Budiarsa Suyasa; I G.A Kunti Sri Panca Dewi (Environmental Research Center (PPLH) of Udayana University, 2008)
The research was conducted about dirt pig compost with variation of composition, Toksicity of it was detected by influence to Growth Of Lombok Rawit ( Capsicum Frutescens). The composition of it is I ( pig dirt 40%, hay 40%, dregs know 18%, dolomit 20%), II ( pig dirt 60%, hay 22%, dregs know 13%, dolomit 2%), and III ( pig dirt 70%, hay 13%, dregs know 15%, dolomit 2%). Growth of microorganism in compost process cover two phase that is ferment phase and maturation Process of composting with composition of III ( pig dirt 70%, hay 13%, dregs know 15%, dolomit 2%) owning best quality. That shown from speed of maturation time posed at stability of temperature and pH reached at period six week, influence to growth of lombok rawit ( Capsicum Frutescens) tried give best level of growth that seen amount of leaf more than composition I and II.